An Introduction to Analog and Digital Communications (sách photo) - Haykin Simon (American : Wiley, 1989)
An introductory treatment of communication theory as applied to the transmission of information-bearing signals with attention given to both analog and digital communications. Chapter 1 reviews basic concepts. Chapters 2 through 4 pertain to the characterization of signals and systems. Chapters 5 through 7 are concerned with transmission of message signals over communication channels. Chapters 8 through 10 deal with noise in analog and digital communications. Each chapter (except chapter 1) begins with introductory remarks and ends with a problem set. Treatment is self-contained with numerous worked-out examples to support the theory.
Solutions Manual and Teacher's Manual available.
The publisher, John Wiley & Sons
Keywords: Điện tử - Viễn thông; Digital Comunications; Telecommunication systems